PENINGKATAN KUALITAS PELAYANAN PUBLIK MELALUI PENERAPAN GOOD GOVERNANCE PADA BADAN PENDAPATAN DAERAH KOTA KENDARI - Adrian Tawai; Muhammad Amir; Almaidah (Journal Publicuho, 2023)
This study aims to describe how good governance is implemented in order to improve the quality of public services at the Kendari City Regional Revenue Agency. This study used a qualitative descriptive research type with six informants. Data collection techniques start from direct observation, interviews, and documentation. Data analysis techniques used are data collection, data reduction, data presentation and conclusion and verification. The results of the study show that transparency has not been implemented properly, where the requirements for service are only found at the front office and there are no billboards or information boards so that people often ask questions about these requirements. However, from the dimension of responsiveness related to the ability to respond, it is said to be good in providing services, it is said to be fast and to act fairly by serving the community according to the queue number obtained. Meanwhile, from the indicators of effectiveness and efficiency, employees are disciplined in providing services and following service procedures. Meanwhile, from the accountability dimension, employees are responsible by reprimanding and directing staff if negligence occurs.